Insights into variations of seasonal and daily soil temperatures under the effect of biocrusts in central-western Argentina - Navas Romero, Ana Laura; Herrera Moratta, Mario; Martínez-Carretero, Eduardo; Vento, Barbara; Fernández-Belmonte, María C. (Instituto de Ecología, A.C., 2023)
Background and Aims: Biocrusts play an essential role on the earth’s surface and have a direct influence on soil parameters. Their effects on soil temperature are considered one of the most important because they affect ecological and hydrological processes, as well as the diversity of natural ecosystems. Although there are several studies concerning biocrust effects on the soil surface, investigations about the effect of the biocrust on soil temperature are still scarce. Our objective was to evaluate the influence of biocrusts on soil temperature conditions in drylands of central-western Argentina. Methods: Temperature values were recorded in the Monte phytogeographic region in the central-western part of Argentina, in three sites, during the dry and wet seasons in 2017-2018. We collected samples from a total of 30 randomly selected plots. We recorded daily temperatures values in two paired plots with crusted and uncrusted zones using a calibrated data logger Ibutton. The sampling took 18 days in total, three days on each site.Key results: Our results indicate that biocrusts produce a change in micro-soil temperatures. Areas in which biocrusts are present show a temperature reduction both in the wet and dry seasons. This effect is observed in the three studied sites. Temperature reduction varies according to the time of the day, study site and season. The morning, noon, and afternoon recorded the highest mean temperatures.Conclusions: The presence of biocrusts reduces soil temperatures in drylands of central-western Argentina. Large differences in mean temperature values between crusted and uncrusted zones were observed. The thermal reduction was more notorious in the hyper-arid site. How they affect their surrounding environment can be related to multiple factors, such as the composition of the microphytic community, the local climate and environmental conditions.